Hydrothermal syntheses of ETS-10 like vanadosilicates using chiral organic molecules. Part I - Paula, Alex S. [UNESP]; de Vasconcellos, Adriano [UNESP]; Ellena, Javier A.; Giotto, Marcus; Nery, Jose G. [UNESP] (Elsevier B.V., 2012)
Vanadosilicates with the structures of ETS-10 and AM-6 microporous materials have been hydrothermally synthesized using organic directing structures agent (SDAs) derivatives of decahydroquinoline, 3,5-dimethyl-piperidine, 2,6-dimethyl-piperidine and (S)-Sparteine. Derivatives of these chiral amines have not been explored before in the sot gel chemistry of vanadosilicates. Physicochemical characterization of the obtained vanadosilicate materials with these different chiral templates was carried out by Xray diffraction (XRD), scanning electron microscopy (SEM). Raman and infrared (IR) spectroscopy, solid-state NMR spectroscopy, and differential thermogravimetric analysis (DTA)/thermogravimetric analysis (TGA). The results suggest that the presence of the chiral organic templates have different effects in terms of the final phase of the synthesized materials and their morphology. The products obtained using chiral template derivatives of decahydroquinoline reveal that certain products might be very enriched with chiral polymorph A while others present structures which are similar to other large-porous vanadosilicate such as AM-6 and AM-13. Derivatives of 2,6-dimethyl-piperidine and 3,5-dimethyl-piperidine have not favored any structure that resembles a chiral polymorph A. but only known vanadosilicates such as AM-6, AM-13. Derivatives of (S)-Sparteine, on the other hand, have not only favored the formation of structures enriched with a large amount of chiral polymorph A, but also their use has resulted in other unknown vanadosilicate structures whose physicochemical characterizations are in progress. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: AM-6; Chiral polymorph of ETS-10; Structure directing agent; (S)-Sparteine; Decahydroquinoline